Optical Coherence Tomography Angiography (OCTA) information content in the diagnosis of type 1 choroidal neovascularization combined with pigment epithelium detachment - V. V. Neroev; M. V. Ryabina; A. P. Sarygina (Российский офтальмологический журнал)
Purpose of the study is to determine the reliability of OCT angiography in the diagnosis of type 1 choroidal neovascularization (CNV) in wet age-related macular degeneration depending on the height of pigment epithelium detachment (PED).Material and methods. The study included 82 patients (114 eyes) with confirmed type 1 CNV, who were examined using spectral OCT and OCTA. The patients were divided into two groups depending on PED height: group 1 consisted of 69 eyes with PED height less than 300 μm, while group 2 (45 eyes) had PED height of more than 300 μm. A separate comparative analysis of the visualization of pathological vessels was made in a group of untreated patients (56 eyes) and a group of patients (58 eyes) treated with angiogenesis inhibitors.Results. In group 1 with a PED height less than 300 μm (167.0 ± 60.4 μm) OCTA detected blood flow along abnormal vessels in 100 % of cases. In group 2 with a PED height above 300 μm (484.7 ± 131.9 μm) CNV vessels were visualized in 24.4 % of eyes. The PED height of patients after intravitreal injections of angiogenesis inhibitors (IVI IA) ranged from 38 to 683 μm (221 ± 133 μm). According to OCTA visualization of type 1 CNV vasculature was noted in 55 eyes (94.8 %). In patients who received no antiangiogenic therapy, with a PED height 59 - 800 μm (238 ± 149 μm) CNV was visualized in 41 % of cases (23 eyes).Conclusion. OCTA showed high reliability in the diagnosis of type 1 CNV with low PED. This method was significantly less informative when the height of the neovascular PED exceeded 300 μm, with the exception of PED after IVI IA.